2003
DOI: 10.1046/j.1525-1438.2003.13017.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with stereotactic radiosurgery for brain metastases of endometrial carcinoma: A case report and review of the literature

Abstract: Brain metastases from endometrial carcinomas are rare and the treatment is usually difficult. Here, we report a patient with stage IV endometrial carcinoma whose brain metastases showed complete remission after stereotactic radiosurgery using a gamma-knife. A 48-year-old woman underwent removal of a single brain metastatic lesion, and one month later underwent hysterectomy for endometrioid-type G3, endometrial adenocarcinoma. After hysterectomy, a cranial magnetic resonance imaging (MRI) demonstrated multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…87,88 In addition, for brain metastases, stereotactic radiotherapy showed to be a good alternative for whole brain radiotherapy, with less risk of neurocognitive damage. 89,90 CONCLUSIONS Our efforts should focus on defining the optimal treatment of primary endometrial cancer to prevent recurrences in the first Table 1, recommendations for the management of patients with recurrent endometrial cancer are proposed. These recommendations are based on the available evidence in the literature, which consists in most cases only of level of evidence IV.…”
Section: Distant Recurrencementioning
confidence: 99%
“…87,88 In addition, for brain metastases, stereotactic radiotherapy showed to be a good alternative for whole brain radiotherapy, with less risk of neurocognitive damage. 89,90 CONCLUSIONS Our efforts should focus on defining the optimal treatment of primary endometrial cancer to prevent recurrences in the first Table 1, recommendations for the management of patients with recurrent endometrial cancer are proposed. These recommendations are based on the available evidence in the literature, which consists in most cases only of level of evidence IV.…”
Section: Distant Recurrencementioning
confidence: 99%
“…Factors examined for their possible association with CNS metastasis from endometrial cancer have included unfavorable clinical disease stage or high-grade tumor (109,110) , lymph node involvement (111) , deep myometrial invasion (108) , cervical involvement (108,110) , and lymphovascular space invasion (109,110) . Cases in which the tumor is high grade and lymphovascular space invasion and deep myometrial invasion are present may be more prone to metastasize earlier in the course of the disease (108) .…”
Section: Cns Metastasesmentioning
confidence: 99%
“…This review revealed 16 patients from nine published studies who underwent surgery for brain metastases from endometrial cancer (107)(108)(109)(110)(112)(113)(114)(115)(116) (Table 7). Six of seven patients with stage IV disease had brain metastasis at diagnosis, and the seventh developed brain metastasis 3 months after bone metastasis at primary diagnosis.…”
Section: Cns Metastasesmentioning
confidence: 99%
See 2 more Smart Citations